2020
DOI: 10.1101/2020.07.02.184424
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A clinically-relevant polymorphism in the Na+/taurocholate cotransporting polypeptide (NTCP) occurs at a rheostat position

Abstract: AbstractConventionally, most amino acid substitutions at important protein positions are expected to abolish function. However, in several soluble-globular proteins, we identified a class of non-conserved positions for which various substitutions produced progressive functional changes; we consider these evolutionary “rheostats”. Here, we report a strong rheostat position in the integral membrane protein, Na+/taurocholate cotransporting polypeptide (NTCP), … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…The structural data for I98X variants are consistent with the idea that the structure around a rheostat position accommodates a range of side chain types. Similar accommodations were computationally predicted for multiple variants at a rheostat position in the E. coli lactose repressor protein 14 and the sodium taurocholate co‐transporting polypeptide 5 …”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The structural data for I98X variants are consistent with the idea that the structure around a rheostat position accommodates a range of side chain types. Similar accommodations were computationally predicted for multiple variants at a rheostat position in the E. coli lactose repressor protein 14 and the sodium taurocholate co‐transporting polypeptide 5 …”
Section: Discussionsupporting
confidence: 52%
“…Understanding how each position of a protein contributes to function is central to such diverse applications as interpreting exome sequencing in personalized medicine and engineering novel protein functions for biotechnology. We previously showed that many proteins contain a class of amino acid positions with special abilities to alter protein function 1–6 . At these “rheostat” positions, substituting a range of amino acid types results in a striking continuum of functional outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of their defining features is that, when individually substituted with a range of amino acids, various functional parameters (e.g., binding affinity, allosteric regulation) are modulated. Indeed, the functional range for each position can span several orders of magnitude 3–7 . As such, substitutions at these “rheostat” positions provide ready opportunities for fine‐tuning function during evolution and protein engineering.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative approach, we agnostically, but systematically, substituted nonconserved positions with a wide variety of amino acids. This strategy revealed a class of functionally-important positions with substitution outcomes that differed strikingly from textbook expectations ( Supplementary Figure 1; (14)(15)(16)(17)(18)(19)(20)). For this new class of "rheostat" positions, a key feature is their ability to modulate function (e.g.…”
mentioning
confidence: 81%